Oxygen Diode Formed in Nickelate Heterostructures by Chemical Potential Mismatch. Issue 15 (7th March 2018) - Guo, Er‐Jia; Liu, Yaohua; Sohn, Changhee; Desautels, Ryan D.; Herklotz, Andreas; Liao, Zhaoliang; Nichols, John; Freeland, John W.; Fitzsimmons, Michael R.; Lee, Ho Nyung
Abstract: Deliberate control of oxygen vacancy formation and migration in perovskite oxide thin films is important for developing novel electronic and iontronic devices. Here, it is found that the concentration of oxygen vacancies (VO ) formed in LaNiO3 (LNO) during pulsed laser deposition is strongly affected by the chemical potential mismatch between the LNO film and its proximal layers. Increasing the VO concentration in LNO significantly modifies the degree of orbital polarization and drives the metal–insulator transition. Changes in the nickel oxidization state and carrier concentration in the films are confirmed by soft X‐ray absorption spectroscopy and optical spectroscopy. The ability to unidirectional‐control the oxygen flow across the heterointerface, e.g., a so‐called "oxygen diode", by exploiting chemical potential mismatch at interfaces provides a new avenue to tune the physical and electrochemical properties of complex oxides. Abstract : Deliberate control of oxygen vacancies in nickelate heterostructures is achieved by combining perovskite oxides with dissimilar chemical potentials. The discovery of a precise tuning knob to achieve the unidirectional control of oxygen flow across the heterointerface coins the concept of an "oxygen diode."